Knowledge and Attitude towards Euthanasia among UNIMAS Undergraduate Nursing Students - ABDUL RAHMAN, NUR IZDIHAR; KAUSHAL, DEV NATH (Trends in Undergraduate Research, 2024)
Euthanasia is a controversial and ethically debated topic, stirring intense discussion and moral dilemmas in the medical field. This study aims to assess the knowledge and attitude towards euthanasia amongst Universiti Malaysia Sarawak (UNIMAS) undergraduate nursing students and to examine the association between knowledge and attitude towards euthanasia. 148 undergraduate nursing students from UNIMAS responded to an online self-administered questionnaire on knowledge and attitude towards euthanasia adapted from Portilla et al (2021) and Wasserman et al (2005) respectively. The results revealed that 78.4% of participants possessed good knowledge levels regarding euthanasia. However, more than half of the participants (50.7%) exhibited poor attitudes towards euthanasia. There were no significant associations between knowledge and attitudes among undergraduate nursing students towards euthanasia. The findings highlight the importance of strengthening education and ethical guidance for nursing students, to prepare then to encounter morally challenging situations that call for their best moral judgment. This study emphasizes the need for appropriate and targeted interventions to promote understanding and fostering empathetic decision-making skills among undergraduate nursing students to navigate such a sensitive domain of moral-ethical issue ensuring optimal patient care delivery and ethical practice.